Production and preclinical assessment of camelid immunoglobulins against Echis sochureki venom from desert of Rajasthan, India. (August 2017) - Tanwar, P.D.; Ghorui, S.K.; Kochar, S.K.; Singh, Raghvendar; Patil, N.V.
Abstract: Snakebite is a significant cause of death and disability in subsistent farming populations of rural India. Antivenom is the most effective treatment of envenoming and is manufactured from IgG of venom-immunised horses. Because of complex fiscal reasons, the production, testing and delivery of antivenoms designed to treat envenoming by the most medically-important snakes in the region has been questioned time to time. In this study, we report successful immunisation of dromedaries ( Camelus dromedarius ) against the venom of Indian saw-scaled Viper- Echis carinatus sochureki . This study assessed the specificity and potential of camels immunised with venom of medically most important snake of Western India, the saw-scaled viper ( Echis c. sochureki ). Using WHO standard pre-clinical in vivo tests the neutralisation of the venom responsible for the lethal, haemorrhagic, coagulant and local necrotizing activities were measured, since these are the most significant effects that characterize envenoming by this species. The anti-venom was found significantly effective in the neutralisation of all these effects tested and thus, revealed further an immunological perspective, that camel IgG anti-venom (monospecific) would be as efficacious as specific equine anti-venoms or even of better choice in treating snake specific envenoming. Highlights: The present study is an attempt to raise the IgG against venom of E.c. sochureki, a newly identified sub species in India. It demonstrated that camels immunised with venom produced immunoglobulin of high neutralising capability. Preclinical potency of antivenom was assessed as per WHO guideline/protocols.